2021
DOI: 10.3390/v13112266
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR-155 Promotes TGF-β Mediated Suppression of HIV Release in the Cervical Epithelial Cells

Abstract: TGF-β has been shown to play a differential role in either restricting or aiding HIV infection in different cell types, however its role in the cervical cells is hitherto undefined. Among females, more than 80% of infections occur through heterosexual contact where cervicovaginal mucosa plays a critical role, however the early events during the establishment of infection at female genital mucosa are poorly understood. We earlier showed that increased TGF-β level has been associated with cervical viral shedding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…These findings thus suggest that miR-155 has the potential to regulate the expression of host restriction factors. Similar findings were previously reported by our group, where we showed that miR-155 inhibition increased the expression of APOBEC-3G, IFI-16 and IFITM-3 in cervical epithelial cells [127]. The host restriction factors are the type-1 interferon-induced specialized host proteins that inhibit virus replication at multiple stages [112,[128][129][130] and influence the course of HIV infection and disease outcome [131,132].…”
Section: Discussionsupporting
confidence: 89%
“…These findings thus suggest that miR-155 has the potential to regulate the expression of host restriction factors. Similar findings were previously reported by our group, where we showed that miR-155 inhibition increased the expression of APOBEC-3G, IFI-16 and IFITM-3 in cervical epithelial cells [127]. The host restriction factors are the type-1 interferon-induced specialized host proteins that inhibit virus replication at multiple stages [112,[128][129][130] and influence the course of HIV infection and disease outcome [131,132].…”
Section: Discussionsupporting
confidence: 89%
“…In a prior investigation, a similar expression pattern of miR-182, miR-200c and miR-125b was observed in the serum of HIV-positive women [6]. In contrast, previous research has reported upregulated miR-182 and downregulated miR-146a in HIV-uninfected patients with sepsis, demonstrating signi cant lymphopenia and depleted CD4 and CD8 T-cells [7]. This suggests that the downregulation of miR-182 is HIV-dependent.…”
Section: Discussionmentioning
confidence: 72%
“…The ndings have signi cant implications for understanding the molecular mechanisms underlying cervical cancer risk. Since an earlier study demonstrated that miR-143, miR-145, miR-146a and miR-182 play direct roles in immunological processes [7], this study evaluates the potential utility of these miRNAs as predictive biomarkers for cervical cancer risk assessment and their suitability as therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical epithelial cells are widely believed to support internalizing, transcytosing, and transinfecting CD4-positive cells with HIV-1 [20,21]. The majority of reports indicate that this process takes place without infection of the epithelial cells, the recent reports emphasize that these cells are also susceptible to productive infection with HIV-1 [22][23][24]. The most current reports indicated that bronchial, renal, and gastric epithelial cells could also produce infectious retroviruses as a result of viral transcription and integration [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%